PLACING IDENTITY ON THE MARKET (The Role of Modern Tourism on Kasepuhan Banten Kidul Community’s Cultural Movement in West Java, Indonesia) - Widiyanto, Nur (Kepariwisataan: Jurnal Ilmiah, 2017)
This paper examines the dynamics within the encounter between identity formation of a minority group living in West Java, Indonesia and the arrival of modern tourism in the area. It studies whether an indigenous group endowed by various amazing tourism resources engages with tourism as a tactics to deal with policies excluding them for years. Contrasting to Friedman’s study on the early Hawaiian cultural movement which was anti-tourism, Kasepuhan Banten Kidul community living on Cipta gelar, an enclave area under Halimun-Salak National Park’s control,takes tourism as the opportunity to resist various dominations and to strengthen its cultural identity. Findings from participant’s observations and indepth interview show some changes are also inevitable. Engaging with modern tourism means the readiness to accommodate the arrival of various outside elements. However, the strategy has led local government to declare the area as part of major tourism destination in 2007. It means Sunda Wiwitan, an indigenous religion practiced by the community which is not officially recognized as a legal religion in Indonesia can be freely practiced in order to promote tourism. In this case, tourism is seen as one opportunity to establish a form of social movement in resisting dominations. Borrowing De Certeu, the community might have produced silent productivity to deal with larger authorities, including with its consequences in various ways. Keywords: identity, Kasepuhan Banten Kidul, tourism, resistance